Climatic response of Abies guatemalensis Rehder in Ixtlán de Juarez, Oaxaca, Mexico - Aquino-Ramírez, Martín; Velázquez-Martínez, Alejandro; Villanueva-Díaz, José; Hervert-Zamora, Haidie Lissette; Gomez-Guerrero, Armando; Reyes-Hernández, Valentín José; Ramírez-Valverde, Gustavo (Instituto de Ecología, A.C., 2019)
In Mexico there are tree species, specifically, the group of conifers, which allow to analyze and reconstruct the climatic variations of the past of one or more geographical regions. The objective of this study was to determine the dendrochronological response potential of Abies guatemalensis Rehder. to climatic variability in Ixtlán de Juárez, Oaxaca. Earlywood, latewood and total ring chronologies of 206 years (1810-2015) were developed. The seasonal correlation analysis revealed a direct relationship between the residual RWI chronology with the winter-spring precipitation (r = 0.67, p < 0.01) and an indirect relationship with the maximum spring temperature (r = -0.42, p < 0.01) of the current year of growth. Using a linear regression model, the accumulated precipitation from February to April was reconstructed over the last 136 years (1880-2015), which explained 44% of the variability of the local meteorological records of the calibration period (1952-2010). The driest periods occurred in the 1880´s, 1900´s, 1940´s, 1970´s, 1980´s, 1990´s and 2000´s. The spectral analysis of the reconstruction showed quasi-cyclic periodicity of 2.2 years and 3.8 years, indicating an association with El Niño-Southern Oscillation. The sensitivity of the species to climatic variations reflected in the thickness of its growth rings, suggests that A. guatemalensis has potential for hydroclimatic reconstructions, which will allow to extend in time the instrumental records for broader analyses of fluctuations in the climate and its trends in this region of the country.